Medicine and Practical Ethics in Galen - Xenophontos, Sophia (Cambridge University Press, 2024)
Offering the first authoritative analysis of Galen's psychological and ethical works alongside a large number of technical tracts, both medical and philosophical, this book provides a new framework through which we can comprehend Galen's role as a practical ethicist - an aspect of his intellectual profile that has been little understood until now.